Optimal Mainline Variable Speed Limit Control to Improve Safety on Large‐Scale Freeway Segments. (28th August 2015) - Li, Zhibin; Liu, Pan; Xu, Chengcheng; Wang, Wei
Abstract: The primary objective of this study was to develop a procedure for determining the optimal variable speed limit (VSL) control strategy that aims at reducing both collision risks and injury severity on large‐scale freeway segments. The achieved reduction in collision risks and injury severity were evaluated using real‐time crash risk and severity prediction models. A modified cell transmission model (CTM) that took into consideration the capacity drop and the stop‐and‐go traffic was used to simulate the traffic operations with the VSL control. A computational procedure that incorporated the genetic algorithm and the CTM was proposed for the optimization of critical VSL control factors. Three scenarios with various placements of VSL signs on freeway mainlines were evaluated. The results showed that the optimal VSL control successfully decreased the collision risks by 22.62% and reduced the injury severity of crashes by 14.67%. We also evaluated how drivers' compliance to speed limits affected the effectiveness of VSL control. The safety effects decreased as drivers' compliance rate to the VSL control decreased. The finding suggests the use of speed enforcement techniques together with the VSL control to achieve the optimum control effects.